(untitled) (Journal for the Study of Religion and History (JSRH), 2026)
This article examines Chinese Rosary manuals produced between 1616 and c. 1665 as a case study in early modern Chinese Christian translation and Sino-European cultural encounter. Focusing on the Rosary, an explicitly devotional text rather than a formal biblical translation, the study argues that prayer manuals nonetheless constituted an important site for the transmission and transformation of scriptural language in late Ming and early Qing China. While not biblical translations in the strict sense, these texts incorporated biblical narratives and formulae in ways that confronted many of the same linguistic, conceptual, and doctrinal challenges faced by Bible translation. The analysis proceeds in two stages. First, it compares the Portuguese Rosary original with the earliest Chinese translation (1616), highlighting shifts in intended audience, pastoral needs, and local cultural sensibilities as the text was rendered intelligible within a Chinese literary and religious framework. Second, it compares three extant Chinese versions (1616, 1628, c. 1665), tracing their evolution in style, layout, and translation strategies for liturgical concepts, divine titles, and Catholic personal names. Across these versions, Catholic personal names tend to remain transliterated with relative consistency, while divine titles and liturgical concepts increasingly rely on neologism and semantic extensions, drawing on classical and Neo-Confucian vocabulary. These textual developments reveal a growing orientation toward literati’s intellectual framework and aesthetics, which may have created a gap between literary ambitions and the major devotional audiences according to missionaries’ reports. By situating Chinese Rosary manuals alongside contemporaneous Chinese versions of the Hail Mary and contrasting them with a Rosary text and critiques from other Catholic orders, this study highlights a persistent tension between concerns for doctrinal accuracy and the pragmatic need for cultural accommodation. It argues that devotional texts functioned as a distinctive mode of scriptural mediation, shaped by missionary strategies, literary norms, and pastoral realities in the early Sino-Christian encounter.